Digital image reduction for analysis of topological changes in the pore space of the rock matrix during chemical dissolution - Prokhorov, D.I.; Bazaikin, Ya.V.; Lisitsa, V.V. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2020)
A new algorithm for the reduction of three-dimensional digital images is proposed to improve the performance of persistence diagrams computing. These diagrams represent changes in topology of the pore space in the rock matrix. The algorithm has a linear complexity, since the removal of the voxel is based on the structure of its neighborhood. It is shown that the efficiency of the algorithm depends heavily on the complexity of the pore space and the size of filtering steps.